Impact of Training Program on SHG Members : A Study of DAY-NRLM in Gorakhpur District - Srivastava, Vanshika; Gupta, Ravi Kumar; Singh, Sudhir Narayan (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : Deen Dayal Antodaya Yojana-National Rural Livelihood Mission (DAY-NRLM) is the government's most extensive poverty-reducing scheme, which focuses on eradicating poverty and self-employment. The primary focus is on empowering rural household women of the nation. The government focused on skill development by providing adequate training to the female participants. The paper empirically examined the effect of training on the rural women under DAY-NRLM. Methodology : The paper is based on primary data with a sample size of 385 to conduct the study in the Gorakhpur district of Uttar Pradesh. To measure the training impact of the scheme, the study used descriptive statistics for frequency measurement, a one-sample T-test for evaluating impact, and logistic regression for further analysis. Findings : The results showed that the training had a significantly positive impact on the beneficiaries, as the increased income and better living standards depict the positive outcome. The beneficiaries also showed satisfaction with the training provided by DAY-NRLM. Overall, the scheme demonstrated a positive result and the holistic development of the beneficiaries. Practical Implications : The research enhanced knowledge about the performance of the SHG members regarding training. It also highlighted the gap and the motive to conduct the study. The study mentioned the satisfaction level of the beneficiaries and provided suggestions for future studies. Originality : The study provided evidence calculated through a statistical tool using data from female SHG members of the villages of the Gorakhpur district.